Influence of azelaic acid on acne pathogenesis - A. І\І. Khlebnikova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
I In current literature review the physicochemical properties, peculiarities of mode of action and pharmacokinetics of azelaic and influence of azelaic on pathogenetic aspects of acne are characterized.